MicroRNA‐199a‐5p aggravates angiotensin II–induced vascular smooth muscle cell senescence by targeting Sirtuin‐1 in abdominal aortic aneurysm. Issue 13 (15th June 2021) - Tao, Wuyuan; Hong, Yimei; He, Haiwei; Han, Qian; Mao, Mengmeng; Hu, Bei; Zhang, Hao; Huang, Xiaoran; You, Wei; Liang, Xiaoting; Zhang, Yuelin; Li, Xin
Abstract: Vascular smooth muscle cells (VSMCs) senescence contributes to abdominal aortic aneurysm (AAA) formation although the underlying mechanisms remain unclear. This study aimed to investigate the role of miR‐199a‐5p in regulating VSMC senescence in AAA. VSMC senescence was determined by a senescence‐associated β‐galactosidase (SA‐β‐gal) assay. RT‐PCR and Western blotting were performed to measure miRNA and protein level, respectively. The generation of reactive oxygen species (ROS) was evaluated by H2DCFDA staining. Dual‐luciferase reporter assay was used to validate the target gene of miR‐199a‐5p. VSMCs exhibited increased senescence in AAA tissue relative to healthy aortic tissue from control donors. Compared with VSMCs isolated from control donors (control‐VSMCs), those derived from patients with AAA (AAA‐VSMCs) exhibited increased cellular senescence and ROS production. Angiotensin II (Ang II) induced VSMC senescence by promoting ROS generation. The level of miR‐199a‐5p expression was upregulated in the plasma from AAA patients and Ang II–treated VSMCs. Mechanistically, Ang II treatment significantly elevated miR‐199a‐5p level, thereby stimulating ROS generation by repressing Sirt1 and consequent VSMC senescence. Nevertheless, Ang II–induced VSMC senescence was partially attenuated by a miR‐199a‐5p inhibitor or Sirt1 activator. Our study revealed that miR‐199a‐5p aggravates Ang II–induced VSMC senescence by targeting Sirt1 and that miR‐199a‐5p is a potential therapeutic target for AAA.